Regulation of MT1-MMP and MMP-2 by the Serpin PEDF: A promising new target for metastatic cancer - Alcantara, M.; Dass, Crispin (S. Karger AG, 2013)
The balance of endogenous angiogenic factors in the body is responsible for the homeostatic control of angiogenesis during normal physiological circumstances, with the disruption of this fragile balance leading to pathologic angiogenic events such as those involved in cancer progression. This review focuses regulation of the pro-angiogenic factors membrane type-1 matrix metalloproteinase (MT1-MMP) and matrix metalloproteinase-2 (MMP-2) by the antiangiogenic factor pigment epithelium-derived factor (PEDF) in the contexts of angiogenesis, cancer cell proliferation and metastasis. Understanding the role of PEDF in the regulation of MT1-MMP and MMP-2 as it pertains to cancer control is important in order to understand whether and how such associations provide a novel target for cancer therapy